The determinants of economic growth in Malaysia / Nurul Hiedayah Yusoff - Yusoff, Nurhiedayah (Faculty of Business and Management, 2014)
Economic growth is an indicator used by country in order to measure the economy performance either they are facing good or bad condition in the economy. A change in economy can occur anytime and may affect the development of the country. A stable and good economy condition shows a positive image and able to attract other countries to invest in the country. Hence, to identify the country‟s level of success, it can be measure from their economic growth or stability. Therefore, the purpose of this study was to examine the determinants that affect the economic growth in Malaysia by using quarterly time series data from year 2005 until 2013. The multiple linear regressions were used in this study to analyse the significant relationship between independent variable (consumer expenditure, government expenditure, foreign direct investment, export and exchange rate) towards dependent variable (gross domestic product). The findings suggested that Malaysia‟s economic growth is determined by changes in consumer expenditure, government expenditure, foreign direct investment and export towards gross domestic product.